PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) PEMBELAJARAN MATEMATIKA BERBASIS MIKiR DI PRODI PGMI UIN SUMATERA UTARA MEDAN - Rora Rizky Wandini; Emeliya Sukma Dara Damanik; Nurdiana Nurdiana (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2023)
This study aims to develop a MIKiR-based mathematics learning MFI product. The location of the research was in the PGMI study program, UIN North Sumatra, Medan, with a total of 25 samples. This research was conducted using the Research & Development method which was adopted from Tiagharijan's development theory. From the realization of this method, this research results that this mathematics learning LKM product is declared feasible with the one sample statistic test, namely 82.32, very practical through observation with a percentage of 9.84%, and quite effective with the acquisition of Ngain 0.71 in the high category, and if converted to Ngain is based on Hake.RR, then the interpretation of Ngain's effectiveness is categorized as quite effective.